PEMBUATAN PETA SITUASI SKALA 1 : 500 DUSUN TEGALMIRI DAN PANDANREJO DESA BANYURIPAN KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , IPNU SUPRIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final project describes the implementation of making a map of the situation in field work. The method of measurement were used in making a map of the situation is the terrestrial method that was started by making the mapping framework. The mapping framework included the Horizontal Control Framework and Vertical Control Framework in the sealing closed poligon. The framework of the map will be used as a reference in making the planimetric detail and high point. The result data of planimetric detail and the high point were described by using Surpac software and ArcGIS so it will obtain a map situation in Tegalmiri and Pandanrejo area, Banyuripan Village, Bayat Sub-District, Klaten District, Central Java Povince with 1 : 500 scale. The projection system that was used in this study was the UTM (Universal Transverse Mercator).